Pro-poor tourism routes: the Open Africa experience - Viljoen, Johannes; Viljoen, Francois; Struwig, Jaré (Acta Academica: Critical views on society, culture and politics, 2010)
Tourism development in South Africa has been inconsistent and has failed to fulfil the promises of pro-poor development. Tourism routes have been touted as a promising means of supporting pro-poor tourism. However, in practice, established tourism route models benefit well-resourced establishments and do little to effectively include disadvantaged communities. This article explores the role of tourism routes as a pro-poor tool by outlining the practical problems of both supporting established routes and developing new ones. The Open Africa tourism route development methodology, its limitations, problems and pitfalls are scrutinised by focusing on two Open Africa routes.